Zjednoczenie Polskich Uchodźców w Niemczech wobec emigracji solidarnościowej w latach 1981-1989 - Wolak, Łukasz (Instytut Pamięci Narodowej. Komisja Ścigania Zbrodni przeciwko Narodowi Polskiemu, 2013)
This lecture is an attempt to show the activity of the main organization of Polish refugees in Germany since fifties onwards - Polish Refugees Union in Germany. I will focus on the activity of organization during eighties of the last century, a declining decade of the Union. Those were the years of organizing difficulties, but the activists were stili engaged in help for the new inflow of emigrants from the Polish People's Republic, the so-called "Solidarity Emigration''. The new wave of refugees in notable numbers joined up the PRU and established thriving regional centres, which organized new life for Polish community even after the shutting down of the PRU's central office. "Solidarity Emigration': which arrived to Germany after the imposition of martial law in Polish People's Republic, definitely prolonged the unavoidable declining of Polish Refugees Union. It was the involvement of that last group of refugees, which enabled the organization to endure until late 1980's. The "Solidarity Emigration" was the only originator of PRU activity during that decade.
Keywords: Solidarność Walcząca; Niemcy; uchodźcy; imigranci; Polacy za granicą; emigracja polska; Zjednoczenie Polskich Uchodźców; Związek Polaków w Niemczech; Stowarzyszenie Polskich Kombatantów; Zjednoczenie Polskiego Uchodźctwa Wojennego